New Technologies Challenge the Future of Taxonomy in Orthoptera - Cigliano, María Marta (2010)
A global imperative for the conservation of biodiversity brings into focus the need for taxonomic research. However, this biodiversity crisis is reflected in a parallel taxonomic crisis. Whereas molecular information is increasingly the evidential basis fordelimiting species, revisionarytaxonomy is frequently dismissed as merely 'descriptive' and lacking a hypothesis-driven nature. Phylogenetic classifications are optimal for storing and predicting information, but phylogeny divorced from taxonomy is unrealizable. Taxonomy, systematics, and phylogeny are interwoven, hypothesis-driven sciences with a shared theoretical base. Taxonomic knowledge remains essential to biological research and knowledge acquisition is made urgent by the biodiversity crisis. Taxonomy needs to prepare to take advantage of new information technology capabilities. Rapid advances in bioinformatics have provided unprecedented opportunities to conduct taxonomic research more efficiently; cybertaxonomyisemergingas an exciting new branch. Here we argue the great potential for using the Orthoptera Species File online (http://orthoptera.speciesfile.org/) as a tool for monograph and revisionary studies of Orthoptera and we also draw attention to a method of integrating many cybertaxonomic tools with species descriptions: this to engage both the specialist taxonomic community and a wider public in the gathering and deepening understanding of taxonomic knowledge.